2021
DOI: 10.3390/educsci11030132
|View full text |Cite
|
Sign up to set email alerts
|

Crisis Management in Higher Education in the Time of Covid-19: The Case of Actor Training

Abstract: The impact of Covid-19 placed Higher Education leadership in a state of crisis management, where decision making had to be swift and impactful. This research draws on ethea of mindfulness, actor training techniques, referencing high-reliability organisations (HRO). Interviews conducted by the author with three leaders of actor training conservatoires in Higher Education institutions in Australia, the UK and the USA reflect on crisis management actions taken in response to the impact of Covid-19 on their sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…As a result, education has changed dramatically, with the distinctive rise of elearning, whereby teaching is undertaken remotely and on digital platforms. Research suggests that online learning has been shown to increase retention of information, and take less time, meaning the changes coronavirus have caused might be here to stay [4][5][6][7]. While countries are at different points in their COVID-19 infection rates, worldwide there are currently more than 1.2 billion children in 186 countries affected by school closures due to the pandemic.…”
Section: Online Education During Covid-19 Pandemicmentioning
confidence: 99%
“…As a result, education has changed dramatically, with the distinctive rise of elearning, whereby teaching is undertaken remotely and on digital platforms. Research suggests that online learning has been shown to increase retention of information, and take less time, meaning the changes coronavirus have caused might be here to stay [4][5][6][7]. While countries are at different points in their COVID-19 infection rates, worldwide there are currently more than 1.2 billion children in 186 countries affected by school closures due to the pandemic.…”
Section: Online Education During Covid-19 Pandemicmentioning
confidence: 99%
“…Disregarding the lack of access to infrastructure for pupils and students led to inequities, because some of them could not benefit from education as did those with access to technology [34]. The COVID-19 pandemic period revealed a managerial crisis caused by the lack of correlation between management and the system itself, which showed that there was insufficient knowledge of the problems of the educational system at the level of management structures [35].…”
mentioning
confidence: 99%
“…Leadership in distributed groups has been a topic of study for a couple of decades, however, the global pandemic context has accelerated the incorporation of hybrid or distributed models in most organizations globally (McNamara, 2021). In this way, the need to have group support practices that, on the one hand, contribute to people's loyalty and simultaneously allow groups to achieve the necessary results to maintain the performance of companies is evident.…”
Section: Alongmentioning
confidence: 99%